Bank dividend restrictions and banks' institutional investors - Christian Mücke (Leibniz Institute for Financial Research SAFE, 2023)
This paper studies the impact of banks' dividend restrictions on the behavior of their institutional investors. Using an identification strategy that relies on the within investor variation and a difference in difference setup, I find that funds permanently decrease their ownership shares at treated banks during the 2020 dividend restrictions in the Eurozone and even exit treated banks' stocks. Using data before the introduction of the ban reveals a positive relationship between fund ownership and banks' dividend yield, highlighting again the importance of dividends for European banks' fund investors. This reaction also has pricing implications since there is a negative relationship between the dividend restriction announcement day cumulative abnormal returns and the percentage of fund owners per bank.
Keywords: G12; G21; G23; G28; G35; 330; Dividend Policy; Mutual Funds; Institutional Investors' Ownership; Banking Supervision; COVID-19 Pandemic